Comprehensive analysis of vitreous specimens for uveitis classification: a prospective multicentre observational study. Issue 11 (16th November 2017) - Maruyama, Kazuichi; Inaba, Tohru; Sugita, Sunao; Ichinohasama, Ryo; Nagata, Kenji; Kinoshita, Shigeru; Mochizuki, Manabu; Nakazawa, Toru
Abstract : Purpose: To determine the clinical relevance of vitreous biomarkers in patients with uveitis. Design: Multicentre, prospective, observational study. Setting: Uveitis outpatient clinics of two academic medical centres in Japan. Patient population: This study included 234 eyes of 191 patients with various uveitis aetiologies: definitive sarcoidosis (61 eyes of 46 patients), suspected sarcoidosis (60 eyes of 45 patients), intraocular tumour (34 eyes of 27 patients), viral infection (20 eyes of 18 patients), non-sarcoidosis (16 eyes of 16 patients) and unknown aetiology (43 eyes of 39 patients). Observation procedure: Vitreous samples (taken by pars planta vitrectomy) were analysed with flow cytometry, cytology and multiplex PCR analysis. Main outcome measures: The primary outcome measures were the diagnostic values of various biomarkers (T cells, B cells and pathogen DNA) in vitreous samples. The secondary outcome was visual acuity after vitrectomy. Results: Sarcoidosis showed higher CD4/CD8 or CD4 + measurements than other aetiologies (p<0.01). In samples with viral infection, pathogen DNA was detected, and CD8 + counts were higher than the other aetiologies (p<0.01). Eyes with tumour had higher CD19 + (p<0.05). Non-sarcoidosis had lower CD4/CD8 than sarcoidosis, higher CD8 + than sarcoidosis and lower CD19 + than tumour (p<0.01). Unknown uveitis had lower CD4/CD8 than sarcoidosis (p<0.01), and higher CD4/CD8 than non-sarcoidosis, viral infection or tumour (p<0.001). Visual acuity improved after vitrectomy (p<0.001). Conclusions: Uveitis aetiologies had distinct vitreous biomarker profiles, especially of infiltrating lymphocytes. Analyses of CD4/CD8 ratio, T-lymphocyte and B-lymphocyte subset, and pathogen DNA in vitreous samples have good safety profiles and high diagnostic value for uveitis classification. Trial registration number: UMIN000004980 ; Pre-results.